A manganese-based zinc ion battery positive electrode material and its preparation method and application
By electrodepositing MnO2 on carbon fiber products treated with conductive agent to form a porous sheet structure, the problem of capacity attenuation and poor conductivity of the positive electrode material of zinc ion battery is solved, and the high performance and long life of manganese-based zinc ion battery is achieved.
Patent Information
- Application Number
- CN202110977687.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-24
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2041-08-24
AI Technical Summary
During the discharge/charging process, the cathode material of zinc ion batteries causes structural damage and phase change due to dual electron reaction and large ion migration energy barrier, resulting in capacity attenuation, and the conductivity of traditional materials is poor, affecting battery performance.
The electrodeposition method is used to deposit MnO2 on carbon fiber products treated with conductive agents. Through constant voltage or constant current electrodeposition technology, combined with surfactant and temperature control, a porous sheet-like MnO2 structure is formed to avoid the use of polymer binders. Improve the conductivity and cyclic stability of the material.
The high conductivity and long life of the positive electrode material of manganese-based zinc ion battery are achieved, and the capacity and cycle stability of the battery are improved, especially in flexible zinc ion batteries, which show excellent cycle performance and stability.
Smart Images

Figure CN113745476B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of manganese-based oxide material preparation, and in particular relates to a manganese-based zinc ion battery positive electrode material and a preparation method and application thereof. Background Art
[0002] Considering the environmental pollution and depletion of fossil energy brought about by the rapid economic development, the development of green, environmentally friendly, safe and efficient energy storage devices has attracted widespread attention.
[0003] At present, lithium-ion batteries occupy an important position in the commercial rechargeable battery market; however, due to the limited lithium metal resources, high development costs and the use of organic electrolytes in lithium-ion batteries, traditional lithium-ion batteries are not only bulky, but also cannot be folded. They are prone to thermal runaway during volume changes, leading to serious safety issues, which hinders their development in flexible and wearable electronic devices. In order to meet the growing demand for flexible devices such as wearable electronic devices and roll-up displays, people are paying more and more attention to aqueous batteries. Aqueous zinc-ion flexible batteries based on manganese (Mn) are attractive due to their low cost, abundant zinc resources, the use of aqueous electrolytes to improve battery safety, and the high theoretical specific capacity (820mAh g -1 ) has attracted a lot of research and industry interest, which should be the best choice for wearable devices that consume less energy but require higher safety. For zinc-ion batteries, during the discharge / charge process, due to the two-electron reaction and Zn 2+ Due to the large ionic radius (0.074nm), the zinc storage process must overcome the large ion migration energy barrier and high electrochemical polarization, which leads to structural damage and phase change of the positive electrode material, resulting in rapid capacity decay. Therefore, the positive electrode material is crucial to the overall performance of the battery.
[0004] So far, only a few cathode materials have been studied for Zn 2+ Storage, combined with the current research status at home and abroad, the positive electrode materials used in zinc-ion batteries are divided into the following three categories: manganese-based materials, vanadium-based materials, and Prussian blue analogs (PBAs); among these materials, manganese-based oxides, especially MnO 2 , are considered to be the most promising host materials for aqueous Zn-ion batteries due to their low cost, low toxicity, and corresponding abundance on Earth.
[0005] In order to solve the problems of poor conductivity and rapid capacity decay, it is necessary to develop manganese-based zinc-ion battery positive electrode materials with better performance. Summary of the invention
[0006] The object of the present invention is to provide a manganese-based zinc ion battery positive electrode material and a preparation method and application thereof to solve one or more of the above-mentioned technical problems. The preparation method provided in the first aspect of the present invention can complete the synthesis of a manganese-based zinc ion battery positive electrode material for a flexible zinc ion battery, and can ensure that MnO 2 The structure is porous and relatively dense. The manganese-based zinc ion battery positive electrode material provided in the second aspect of the present invention is used for the positive electrode of a flexible zinc ion battery, has good conductivity, and can improve the capacity and cycle stability of the battery.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing a positive electrode material for a manganese-based zinc ion battery of the present invention comprises the following steps:
[0009] Using the electrodeposition method, MnO is deposited on the carbon fiber product treated with a conductive agent as the substrate. 2 , obtaining manganese-based zinc-ion battery positive electrode material.
[0010] A further improvement of the method of the present invention is that the method of using electrodeposition is to deposit MnO on the carbon fiber product treated with a conductive agent as a substrate. 2 The steps of obtaining the positive electrode material of a manganese-based zinc ion battery specifically include:
[0011] A sedimentation solution is prepared with manganese nitrate, sodium nitrate and potassium citrate;
[0012] The carbon fiber product treated with a conductive agent is placed in the deposition solution, and constant voltage electrodeposition is used for electrodeposition to obtain a manganese-based zinc ion battery positive electrode material; wherein the constant voltage electrodeposition voltage is 1.0 to 1.5V.
[0013] A further improvement of the method of the present invention is that the method of using electrodeposition is to deposit MnO on the carbon fiber product treated with a conductive agent as a substrate. 2 The steps of obtaining the positive electrode material of a manganese-based zinc ion battery specifically include:
[0014] A sedimentation solution is prepared with manganese nitrate, sodium nitrate and potassium citrate;
[0015] The carbon fiber product treated with the conductive agent is placed in the deposition solution, and the constant current electrodeposition method is used for electrodeposition to obtain the positive electrode material of the manganese-based zinc ion battery; wherein the current of the constant current electrodeposition is 7-18 mA / cm -2 .
[0016] A further improvement of the method of the present invention is that before the electrodeposition, it also includes: placing a surfactant in the deposition liquid; when the electrodeposition is carried out, the temperature is 60-100° C. and the time is 30-60 minutes.
[0017] A further improvement of the method of the present invention is that the carbon fiber product is carbon cloth, carbon paper or carbon fiber.
[0018] A further improvement of the method of the present invention is that the conductive agent is acetylene black, carbon spheres, carbon nanotubes or Super-P.
[0019] A further improvement of the method of the present invention is that the step of obtaining the carbon fiber product after the conductive agent treatment comprises:
[0020] A mixed solution of a conductive agent, alcohol and 5% nafion is prepared, and the mixed solution is ultrasonically treated and then sprayed onto a carbon fiber product to obtain a carbon fiber product treated with a conductive agent.
[0021] A further improvement of the method of the present invention is that MnO is deposited on the carbon fiber product treated with a conductive agent as a substrate. 2 Afterwards, the method also includes: cleaning and drying to obtain the final manganese-based zinc-ion battery positive electrode material.
[0022] The present invention discloses a manganese-based zinc ion battery positive electrode material prepared based on the preparation method of the present invention.
[0023] The present invention provides an application of a manganese-based zinc ion battery positive electrode material, which is used as a flexible zinc ion battery positive electrode material; wherein, at 100mA g -1 At this current density, after 240 cycles, the cathode specific capacity can reach 100 mA hg -1 .
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The preparation method of the present invention discloses electrodeposition of MnO on a carbon fiber product treated with a conductive agent. 2 The technical solution is a fast and simple method for preparing positive electrode materials for manganese-based zinc ion batteries; the conductivity of the positive electrode material can be improved by treating with a conductive agent, thereby increasing the capacity and cycle stability of the battery. The preparation method of the present invention can not only complete the synthesis of the positive electrode material of the manganese-based zinc ion battery for the flexible zinc ion battery, but also ensure that the MnO 2 The structure is porous and relatively dense.
[0026] Specifically, the present invention prepares MnO by electrodeposition on a carbon fiber product treated with a conductive agent. 2 Becoming the positive electrode material of a flexible zinc-ion battery not only avoids the use of polymer binders in previous experiments, but also has the advantages of simple operation, low cost, and speed. At the same time, the addition of conductive agents also effectively improves the conductivity of the positive electrode material.
[0027] Specifically, the present invention uses an electrodeposition method to obtain MnO grown in situ on a carbon fiber product under conductive agent treatment. 2 Excellent cycling performance for flexible zinc-ion batteries. Especially carbon spheres embedded in deposited MnO 2 In the case of MnO 2 The porous structures are fused together to prevent MnO 2 The volume expansion during the reaction causes the positive electrode material to fall off and collapse, thereby stabilizing the battery capacity.
[0028] Based on the specific embodiments of the present invention, in the application of the material of the present invention: at 100mA g -1 At the current density, after 105 cycles, the MnO on the carbon fiber product without conductive agent treatment 2 The specific capacity of the positive electrode is only about 50mA hg -1 After 240 cycles, the MnO 2 The specific capacity of the positive electrode can reach about 100mA hg -1 . The MnO on the carbon fiber products treated with carbon balls 2 The specific capacity of the positive electrode can reach about 180mA hg -1 , which has exceeded the MnO on carbon fiber products without conductive agent treatment. 2 MnO on positive electrode and carbon fiber products treated with acetylene black 2 Positive electrode. It has been proved that the conductivity of the positive electrode material can be improved by treating with a conductive agent, thereby increasing the capacity and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art; obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0030] Figure 1 It is a method of the present invention based on different conductive agents MnO 2 Schematic diagram of the preparation method.
[0031] Figure 2 The MnO prepared in Example 1 of the present invention 2 @CC’s scanning electron microscope (SEM).
[0032] Figure 3 AB-MnO prepared in Example 2 of the present invention 2@CC’s scanning electron microscope (SEM).
[0033] Figure 4 The CS-MnO prepared in Example 3 of the present invention 2 @CC’s scanning electron microscope (SEM).
[0034] Figure 5 It is the X-ray diffraction spectrum (XRD) of the positive electrode material prepared in Examples 1, 2 and 3 of the present invention.
[0035] Figure 6 It is an assembly diagram of the positive electrode materials prepared in Examples 1, 2, and 3 of the present invention assembled into a flexible zinc ion battery.
[0036] Figure 7 The positive electrode materials prepared in Examples 1, 2 and 3 of the present invention are assembled into a flexible zinc ion battery, which is -1 Cycling performance at different current densities.
[0037] Figure 8 The positive electrode materials prepared in Examples 1, 2, and 3 of the present invention are assembled into a flexible zinc-ion battery, showing its flexibility under different bending conditions. DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0039] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0040] A method for preparing a positive electrode material for a manganese-based zinc ion battery according to an embodiment of the present invention comprises the following steps:
[0041] The MnO was deposited on the carbon fiber product treated with conductive agent by electrodeposition. 2 , obtaining a manganese-based zinc-ion battery positive electrode material. Exemplarily, the electrodeposition method includes constant voltage electrodeposition and constant current electrodeposition.
[0042] The step of obtaining the carbon fiber product treated with the conductive agent includes: spraying an appropriate amount of the conductive agent onto the carbon fiber product. Exemplarily, the carbon fiber product is carbon cloth, carbon paper and carbon fiber.
[0043] In an exemplary optimization, MnO is deposited on a carbon fiber product treated with a conductive agent as a substrate by an electrodeposition method. 2 Afterwards, the method also includes: soaking and drying, and finally obtaining the manganese-based zinc-ion battery positive electrode material.
[0044] The preparation method provided by the above embodiment of the present invention can complete the synthesis of manganese-based zinc ion battery positive electrode materials for flexible zinc ion batteries, and can ensure that MnO 2 The structure is porous and relatively dense. In addition, the prepared manganese-based zinc-ion battery positive electrode material is used for the positive electrode of a flexible zinc-ion battery, has good conductivity, and can improve the capacity and cycle stability of the battery.
[0045] The present invention is further described in detail below in conjunction with the accompanying drawings:
[0046] Figures 1 to 8 In the process, the carbon cloth in the carbon fiber product is selected as the deposition substrate, and the MnO deposited on the carbon cloth 2 The positive electrode material is marked as MnO 2 @CC, MnO deposited on carbon cloth after acetylene black treatment 2 The cathode material is marked as AB-MnO 2 @CC, MnO deposited on carbon cloth after carbon ball treatment 2 The cathode material is marked as CS-MnO 2 @CC.
[0047] See also Figure 1 The present invention provides a method for preparing a positive electrode material for a manganese-based zinc ion battery, specifically a method based on different conductive agents MnO 2 The preparation method of Figure 1 The experimental steps of the embodiment of the present invention are described. The carbon cloth treated with the conductive agent is subjected to MnO electroplating. 2 Preparation of MnO 2 In-situ growth on a carbon cloth substrate specifically includes the following steps:
[0048] (1) Spraying an appropriate amount of conductive agent onto the carbon fiber product. Specifically, the carbon fiber product is carbon cloth, carbon paper and carbon fiber; illustratively, the conductive agent, alcohol and 5% nafion solution are ultrasonically treated for a period of time according to a volume ratio of 1:150:1.5, and then sprayed onto the carbon fiber product; the conductive agent includes: acetylene black, carbon spheres, carbon nanotubes and Super-P.
[0049] (2) The obtained carbon fiber product treated with a conductive agent is used as a substrate to deposit MnO by an electrodeposition method. 2 ; Wherein, the electrodeposition method includes constant voltage electrodeposition and constant current electrodeposition.
[0050] Specifically, in the electrodeposition method, the voltage of constant voltage electrodeposition is 1.0-1.5V, manganese nitrate, sodium nitrate and potassium citrate are prepared into a deposition solution according to a molar ratio of 20:200:1, and a certain amount of sodium dodecyl sulfate is added, and the electrodeposition is performed at 60-100°C for 30-60 minutes to obtain the desired sample.
[0051] The current of the constant current electrodeposition in the electrodeposition method is 7 to 18 mA / cm -2 Manganese nitrate, sodium nitrate and potassium citrate are prepared into a deposition solution in a molar ratio of 20:200:1, and a certain amount of sodium dodecyl sulfate is added, and the desired sample is obtained by electrodeposition at 60-100°C for 30-60 minutes.
[0052] (3) Finally, after soaking and drying, MnO treated with different conductive agents was obtained. 2 A positive electrode material; a flexible zinc ion battery can be assembled based on the positive electrode material. Exemplarily, during immersion, deionized water is used to clean the residual sedimentation liquid on the surface of the sample. During drying, an oven is used, and the drying temperature is 60 to 80°C.
[0053] In the application of the embodiment of the present invention, MnO deposited on the carbon fiber products treated with different conductive agents is 2 The positive electrode, hydrogel electrolyte and zinc sheet negative electrode are assembled in sequence to form a flexible zinc-ion battery.
[0054] On the basis of strictly following the attempts in the art, the above-mentioned preferred preparation conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention. The raw materials and experimental reagents used in the present invention are all commercially available.
[0055] The present invention uses a method for electrodeposition of carbon fiber products treated with different conductive agents to prepare a manganese-based zinc ion battery positive electrode material for a flexible zinc ion battery. 2 / Mn 2+Oxidation-reduction potential: 1.23V and electrochemical reaction current, MnO is deposited on carbon fiber products by electrodeposition 2 This method can not only complete the synthesis of manganese-based zinc-ion battery positive electrode materials for flexible zinc-ion batteries, but also ensure that the MnO 2 The structure is porous and relatively dense. Compared with the current liquid phase redox method, sol-gel method, hydrothermal synthesis method, and template method, electrochemical deposition of MnO 2 The invention is a fast and simple method for preparing positive electrode materials of manganese-based zinc-ion batteries.
[0056] The MnO deposited after being treated with a conductive agent manufactured by the present invention 2 When used as the positive electrode material for flexible zinc-ion batteries, it exhibits high specific capacity and cycle stability. -1 At the current density, after 105 cycles, the MnO on the carbon fiber product without conductive agent treatment 2 The specific capacity of the positive electrode is only about 50mA hg -1 After 240 cycles, the MnO 2 The specific capacity of the positive electrode can reach about 100mA hg -1 . The MnO on the carbon fiber products treated with carbon balls 2 The specific capacity of the positive electrode can reach about 180mA hg -1 , which has exceeded the MnO on carbon fiber products without conductive agent treatment. 2 MnO on positive electrode and carbon fiber products treated with acetylene black 2 Positive electrode. It has been proved that the conductivity of the positive electrode material can be improved by treating with a conductive agent, thereby increasing the capacity and cycle stability of the battery.
[0057] In summary, the MnO prepared for flexible zinc-ion batteries 2 The positive electrode material is grown on the carbon fiber product by a hydrothermal method, or by mixing the positive electrode material with a polymer binder and then coating it on the carbon fiber product. The addition of the polymer binder hinders the effective utilization of the surface area of the active material. 2 There are many methods for preparing MnO, including liquid phase redox method, sol-gel method, hydrothermal synthesis method, template method, electrochemical deposition method, etc. Among them, electrochemical deposition method has the advantages of simple operation, low cost and rapidity. 2 The method can also reduce the resistance caused by the use of the binder. The present invention discloses a method for preparing a porous sheet structure MnO by electrodeposition on a carbon fiber product treated with a conductive agent. 2The method is a fast and simple method for preparing a positive electrode material for a flexible zinc ion battery. The present invention can not only complete the synthesis of a manganese-based zinc ion battery positive electrode material for a flexible zinc ion battery, but also ensure that the MnO 2 The structure is porous and relatively dense. Specifically, the present invention prepares MnO by electrodeposition on a carbon fiber product treated with a conductive agent. 2 The invention has become the positive electrode material of the flexible zinc ion battery, which not only avoids the use of polymer binders in previous experiments, but also has the advantages of simple operation, low cost, and rapidity. At the same time, the addition of the conductive agent also effectively improves the conductivity of the positive electrode material. Specifically, the present invention uses the electrodeposition method to obtain MnO grown in situ on the carbon fiber product under the treatment of the conductive agent. 2 Excellent cycling performance for flexible zinc-ion batteries. Especially carbon spheres embedded in deposited MnO 2 In the case of MnO 2 The porous structures are fused together to prevent MnO 2 The volume expansion during the reaction causes the positive electrode material to fall off and collapse, thereby stabilizing the battery capacity.
[0058] Example 1
[0059] A method of preparing a conductive agent based on different conductive agents MnO in the embodiment of the present invention 2 The preparation method is used for a flexible zinc ion battery positive electrode, comprising the following steps:
[0060] Carbon cloth (not treated with conductive agent) was used as a substrate to deposit MnO 2 The voltage of the constant voltage electrodeposition in the electrodeposition is 1.2V, the deposition solution is 0.01M manganese nitrate, 0.1M sodium nitrate and 0.5mM potassium citrate, and a certain amount of sodium dodecyl sulfate is electrodeposited at 80°C for 40min to obtain the desired MnO 2 @CC positive electrode material.
[0061] See also Figure 2 , Figure 2 The MnO prepared in Example 1 of the present invention 2 @CC scanning electron microscope (SEM). It can be seen that MnO 2 has been successfully deposited on a carbon cloth substrate and MnO 2 It has a porous flake structure and is relatively dense.
[0062] Example 2
[0063] A method of preparing a conductive agent based on different conductive agents MnO in the embodiment of the present invention 2 The preparation method is used for a flexible zinc ion battery positive electrode, comprising the following steps:
[0064] 15 mg of acetylene black, 2250 μL of alcohol, and 23 μL of 5% nafion solution were ultrasonically treated for 30 min and sprayed onto the carbon cloth. The carbon cloth treated with acetylene black was used as a substrate to deposit MnO 2 The voltage of the constant voltage electrodeposition in the electrodeposition is 1.2V, the deposition solution is 0.01M manganese nitrate, 0.1M sodium nitrate and 0.5mM potassium citrate, and a certain amount of sodium dodecyl sulfate is electrodeposited at 80°C for 40min to obtain the desired AB-MnO 2 @CC positive electrode material.
[0065] See also Figure 3 , Figure 3 AB-MnO prepared in Example 2 of the present invention 2 @CC scanning electron microscope (SEM). It can be seen that the acetylene black particles are covered with a layer of porous sheet-like structure, indicating that the MnO 2 It still has a porous flake structure and is relatively dense.
[0066] Example 3
[0067] A method of preparing a conductive agent based on different conductive agents MnO in the embodiment of the present invention 2 The preparation method is used for a flexible zinc ion battery positive electrode, comprising the following steps:
[0068] 15 mg carbon spheres, 2250 μL alcohol, and 23 μL 5% nafion solution were ultrasonically treated for 30 min and sprayed onto the carbon cloth. The carbon cloth treated with carbon spheres was used as a substrate to deposit MnO 2 The voltage of the constant voltage electrodeposition in the electrodeposition is 1.2V, the deposition solution is 0.01M manganese nitrate, 0.1M sodium nitrate and 0.5mM potassium citrate, and a certain amount of sodium dodecyl sulfate is electrodeposited at 80°C for 40min to obtain the desired CS-MnO 2 @CC positive electrode material.
[0069] See also Figure 4 , Figure 4 The CS-MnO prepared in Example 3 of the present invention 2 @CC scanning electron microscopy (SEM). It can be seen that part of the carbon spheres have been embedded in MnO 2 In the deposited layer, the porous carbon sphere structure and MnO 2 The flake structures fuse with each other.
[0070] See also Figures 5 to 8 :
[0071] Figure 5 It is the X-ray diffraction spectrum (XRD) of the positive electrode material prepared in Examples 1, 2 and 3 of the present invention. It can be seen that MnO 2@CC、AB-MnO 2 @CC and CS-MnO 2 @CC The positive electrode materials are all amorphous structures, so their surfaces have more active sites, so amorphous materials have superior structural stability and fast reaction kinetics during battery charging and discharging.
[0072] Figure 6 FIG. 1 is an assembly diagram of the positive electrode materials prepared in Examples 1, 2, and 3 of the present invention assembled into a flexible zinc ion battery. It can be seen that the flexible quasi-solid-state rechargeable aqueous zinc ion battery is composed of MnO 2 @CC、AB-MnO 2 @CC and CS-MnO 2 @CC is composed of a positive electrode, a Zn sheet negative electrode and an aqueous electrolyte gel, and is used to test the electrochemical performance of the battery.
[0073] Figure 7 The positive electrode materials prepared in Examples 1, 2 and 3 of the present invention are assembled into a flexible zinc ion battery, which is -1 Cyclic performance under current density. It can be seen that CS-MnO 2 @CC as a positive electrode material for flexible zinc-ion batteries exhibits higher cycle stability and battery capacity, and MnO is deposited on carbon cloth treated with a conductive agent. 2 The application of positive electrode materials in flexible zinc-ion batteries can greatly improve the electrochemical performance of the batteries.
[0074] Figure 8 The positive electrode materials prepared in Examples 1, 2, and 3 of the present invention are assembled into flexible zinc-ion batteries, and the flexible display diagrams under different bending conditions are shown. It can be seen that the physical display diagrams of the flexible zinc-ion battery under different bending degrees show its potential for application in wearable devices.
[0075] Example 4
[0076] A method of preparing a conductive agent based on different conductive agents MnO in the embodiment of the present invention 2 The preparation method is used for a flexible zinc ion battery positive electrode, and the only difference from Example 3 is that 15 mg of carbon balls are changed to 20 mg of carbon balls, and the solution is prepared according to a volume ratio of 1:150:1.5, and the rest is exactly the same as Example 3.
[0077] Example 5
[0078] A method of preparing a conductive agent based on different conductive agents MnO in the embodiment of the present invention 2The method for preparing the positive electrode of the flexible zinc ion battery is used, and the difference from Example 3 is that the voltage of the constant voltage electrodeposition in the electrodeposition is changed from 1.2V to 1.5V; the deposition temperature is changed from 80°C to 100°C; the deposition time is changed from 40min to 60min. The rest is exactly the same as Example 3.
[0079] Example 6
[0080] A method of preparing a conductive agent based on different conductive agents MnO in the embodiment of the present invention 2 The method for preparing the positive electrode of the flexible zinc ion battery is used, and the difference from Example 3 is that the voltage of the constant voltage electrodeposition in the electrodeposition is changed from 1.2V to 1.0V; the deposition temperature is changed from 80°C to 60°C; the deposition time is changed from 40min to 30min. The rest is exactly the same as Example 3.
[0081] Example 7
[0082] A method of preparing a conductive agent based on different conductive agents MnO in the embodiment of the present invention 2 The preparation method is used for the positive electrode of a flexible zinc ion battery, and the difference from Example 3 is that the constant voltage electrodeposition is changed to constant current electrodeposition, and the current is 7 mA / cm -2 ; Others are exactly the same as in Example 3
[0083] Example 8
[0084] A method of preparing a conductive agent based on different conductive agents MnO in the embodiment of the present invention 2 The preparation method is used for the positive electrode of a flexible zinc ion battery, and the difference from Example 7 is that the carbon spheres are replaced with carbon nanotubes; the current is 10 mA / cm -2 ; The temperature is 60°C, the time is 60 min, and the others are exactly the same as in Example 7.
[0085] Example 9
[0086] A method of preparing a conductive agent based on different conductive agents MnO in the embodiment of the present invention 2 The preparation method is used for the positive electrode of a flexible zinc ion battery, and the difference from Example 7 is that the current is 18 mA / cm -2 ; The temperature is 100°C, the time is 30 min, and the rest is exactly the same as Example 7.
[0087] Example 10
[0088] A method of preparing a conductive agent based on different conductive agents MnO in the embodiment of the present invention 2 The preparation method is used for a flexible zinc ion battery positive electrode, and the only difference from Example 7 is that the carbon nanotubes are changed to Super-P; the rest is exactly the same as Example 3.
[0089] In summary, the embodiment of the present invention provides a method based on different conductive agents MnO2 The invention relates to a preparation method for a flexible zinc ion battery positive electrode, and belongs to the technical field of manganese-based oxide material preparation. The method comprises spraying an appropriate amount of conductive agent onto a carbon fiber product; using the obtained carbon fiber product treated with the conductive agent, depositing MnO on the carbon fiber product as a substrate by an electrodeposition method. 2 Finally, after soaking and drying, MnO treated with different conductive agents was obtained. 2 The positive electrode material is assembled into a flexible zinc-ion battery. This avoids the use of polymer binders in previous experiments and has the advantages of simple operation, low cost, and rapidity. 2 The structure is porous and relatively dense. The process of the invention is integrated and fast, and the conductivity of the positive electrode material can be improved after treatment with a conductive agent, thereby improving the cycle stability of the battery. It has potential commercial prospects in flexible devices such as wearable electronic devices and roll-up displays.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a positive electrode material for a manganese-based zinc ion battery, characterized in that: The following steps are involved: By using the electrodeposition method, MnO2 is deposited on the carbon fiber product treated with a conductive agent as a substrate to obtain a manganese-based zinc ion battery positive electrode material; The method of using electrodeposition to deposit MnO2 on a carbon fiber product treated with a conductive agent as a substrate to obtain a manganese-based zinc ion battery positive electrode material specifically includes: preparing a deposition solution with manganese nitrate, sodium nitrate and potassium citrate; placing the carbon fiber product treated with a conductive agent into the deposition solution, and performing electrodeposition by a constant voltage electrodeposition method to obtain a manganese-based zinc ion battery positive electrode material; wherein the voltage of the constant voltage electrodeposition is 1.0~1.5V; or, the method of using electrodeposition to deposit MnO2 on a carbon fiber product treated with a conductive agent as a substrate to obtain a manganese-based zinc ion battery positive electrode material specifically includes: preparing a deposition solution with manganese nitrate, sodium nitrate and potassium citrate; placing the carbon fiber product treated with a conductive agent into the deposition solution, and performing electrodeposition by a constant current electrodeposition method to obtain a manganese-based zinc ion battery positive electrode material; wherein the current density of the constant current electrodeposition is 7~18mA / cm 2 ; The carbon fiber product is carbon cloth, carbon paper or carbon fiber; the conductive agent is carbon sphere; Before the electrodeposition is performed, the method further includes: placing a surfactant in the deposition solution; When conducting electrodeposition, the temperature is 60~100°C and the time is 30~60min; The step of obtaining the carbon fiber product treated with the conductive agent comprises: preparing a mixed solution of the conductive agent, alcohol and 5% nafion, and spraying the mixed solution onto the carbon fiber product after ultrasonic treatment to obtain the carbon fiber product treated with the conductive agent; The manganese-based zinc ion battery positive electrode material prepared by the preparation method is used as a flexible zinc ion battery positive electrode material, and the manganese-based zinc ion battery positive electrode material ... -1 At this current density, after 240 cycles, the positive electrode specific capacity can reach 180 mAh g -1 .
2. The method for preparing a manganese-based zinc ion battery positive electrode material according to claim 1, characterized in that: After depositing MnO2 on the carbon fiber product treated with the conductive agent as a substrate, the method further comprises: The final manganese-based zinc-ion battery positive electrode material is obtained by washing and drying.
3. A manganese-based zinc ion battery positive electrode material prepared by the preparation method according to claim 1 or 2.
Citation Information
Patent Citations
Porous carbon / manganese dioxide composite electrode, preparation method of porous carbon / manganese dioxide composite electrode and rechargeable zinc-manganese ion battery
CN105390697A
Gas diffusion electrode and preparation and application thereof
CN105576264A